Phosphorus fertility and the physiological response of creeping bentgrass and annual bluegrass - Lloyd, Daniel (My University, 2008)
Creeping bentgrass (Agrostis stolonifera) is the preferred turfgrass species for golf course putting greens because of its high shoot density and tolerance for low mowing which results in a smooth, fast playing surface. Annual bluegrass (Poa annua) is another grass tolerant of low mowing and is a major invasive weed in creeping bentgrass putting greens. This research project was performed to evaluate possible physiological differences between the two grasses with respect to phosphorus uptake. This greenhouse experiment examined the two species of grass grown in two different sand types using four different phosphorus treatments. The treatments were chosen to represent different forms of phosphorus with varying degrees of availability. Different soils were used to explore how differences in root zone mineralogy affected phosphorus availability. Forty-two plants were established from seed and evaluated over a ten-week period. Clippings, shoots, and roots were compared based on dry weight and tissue concentrations for phosphorus. The readily available phosphorus treatments showed increased root mass, clipping yield and greater turfgrass quality than the less available phosphorus treatments regardless of grass type. Differences between grass types across the various P levels were not consistently significant. The different root zones exhibited little effect on quality. This study suggests that the manipulation of soil P levels may not be an effective strategy to minimize annual bluegrass invasion as has previously been suggested.
16 p.
Keywords: Soil Science; Agricultural Sciences—Production Systems